2008
DOI: 10.1128/iai.01224-07
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Regulation of Salmonella Pathogenicity Island 1 (SPI1) and SPI4 in Salmonella enterica Serovar Typhimurium

Abstract: Salmonella enterica serovar Typhimurium harbors five pathogenicity islands (SPI) required for infection in vertebrate hosts. Although the role of SPI1 in promoting epithelial invasion and proinflammatory cell death has been amply documented, SPI4 has only more recently been implicated in Salmonella virulence. SPI4 is a 24-kb pathogenicity island containing six open reading frames, siiA to siiF. Secretion of the 595-kDa SiiE protein requires a type I secretory system encoded by siiC, siiD, and siiF. An operon p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 90 publications
5
86
0
Order By: Relevance
“…If R. insecticola 5.15 directly infects the wasp larva, then it must invade orally through the gut and/or through its cuticle. Different cell types and modes of bacterial infection can result in differential regulation of pathogenicity-related factors, as known for O-antigen adhesions that recognize and attach to specific eukaryotic cells (Jacques 1996), the SPI-1 T3SS that is important for invading certain host cells (Main-Hester et al 2008), and signal-transduction systems such as PhoP-PhoQ (Groisman and Mouslim 2006). One way that bacterial pathogens can achieve virulence is by disabling, resisting, or interfering with their host's innate immune system via T3SS effectors such as YopJ and/or O-antigens.…”
Section: Discussionmentioning
confidence: 99%
“…If R. insecticola 5.15 directly infects the wasp larva, then it must invade orally through the gut and/or through its cuticle. Different cell types and modes of bacterial infection can result in differential regulation of pathogenicity-related factors, as known for O-antigen adhesions that recognize and attach to specific eukaryotic cells (Jacques 1996), the SPI-1 T3SS that is important for invading certain host cells (Main-Hester et al 2008), and signal-transduction systems such as PhoP-PhoQ (Groisman and Mouslim 2006). One way that bacterial pathogens can achieve virulence is by disabling, resisting, or interfering with their host's innate immune system via T3SS effectors such as YopJ and/or O-antigens.…”
Section: Discussionmentioning
confidence: 99%
“…H-NS has been shown to repress the transcription of hilA, a number of its activators, and other horizontally acquired SPIs (38,46,48,49,53). We hypothesized that the upregulation of hns in the fur-deficient cells may explain the observed Fur-dependent expression of hilA (Fig.…”
Section: Vol 193 2011mentioning
confidence: 99%
“…It has been reported that, in S. Typhimurium, a deletion of hns is lethal, and certain mutations in the alternative sigma factor (rpoS low ) can compensate for this lethality (38,46,53). Therefore, we used P22 transduction to move hilA-lacZ into strains WN153 (rpoS low ) and WN341 (rpoS low ⌬hns) that were derived from 14028s (38,46). We then introduced the ⌬fur mutation into each strain to eliminate Fur expression.…”
Section: Vol 193 2011mentioning
confidence: 99%
“…Activation of the SPI1 rtsA gene only requires the AraC family activators HilC and HilD if both H-NS and Hha are present [64,65]. The SPI1-encoded transcriptional activator HilA not only promotes expression of SPI1 genes but also appears to counter H-NS silencing of the SPI4 pathogenicity island [66], which acts in concert with SPI1 during Salmonella interactions with the host intestinal mucosa [67]. A requirement for the transcriptional activator SsrB for SPI2 expression is reduced in the absence of H-NS, suggesting that SsrB both activates transcription and relieves H-NS-mediated repression [68].…”
Section: Counter-silencing Of H-ns and Its Functional Consequencesmentioning
confidence: 99%